Pharmacological Activation of the HIF Pathway Exerts Distinct Proliferative Effects in MDA‐MB‐231 and MCF7 cells. Issue 24 (22nd June 2022) - Chan, Yan Ying; Chan, Mun Chiang
Abstract: Hypoxia‐mimicking agents (HMAs) are molecules or compounds used to mimic hypoxia via the activation of the hypoxia‐inducible factor (HIF) pathway. HMAs have been reported to exert both pro‐ and anti‐proliferative in human breast cancer cell lines, although the reason for such dichotomy remains unclear. To investigate this, we first studied the proliferative effects of HMAs using metabolic‐based MTT assay in comparison to manual cell counting. The MTT assay did not reproduce the results from manual cell counting, suggesting that such metabolic‐based assays are unreliable in studies involving the hypoxia pathway. Next, using the manual cell counting method, we investigated the effects of HMAs with distinct mechanisms of action, including IOX2, a well‐characterised and selective inhibitor of the HIF prolyl‐hydroxylases (PHDs). All tested HMAs inhibit proliferation of MCF7 cells but induced proliferation of MDA‐MB‐231 cells to a certain extent. The results show that the HMAs affect proliferation of human breast cancer cells, likely via upregulation of HIF. The effects of HIF activation on cancer cell proliferation are important given the ongoing clinical trials of inhibitors targeting the PHDs for the treatment of anaemia. Abstract : Hypoxia‐mimicking agents (HMAs) exert distinct proliferative effect on breast cancer cells depending on the subtype. Pharmacological HIF activation via PHD inhibition enhances the proliferation rate of triple negative MDA‐MB‐231 cells but inhibits proliferation of receptor‐positive MCF7 cells. Therefore, clinical PHD inhibitors should be used with caution as they may be a double‐edged sword, acting as anticancer agents or tumorigenic drivers depending on the breast cancer subtype.